The Effects of Company Size, Business Diversification, and Investment Decision on Firm Value with Capital Structure as a Moderating - Thia Margeretha Tarigan; Novia Utami; Selvi Arifin (Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This research aims at reviewing whether company size, business diversification, and investment decision affect firm value by using capital structure as a mediator. Samples were collected from a population (all manufacturing companies listed in Indonesia Stock Exchange within observation period of 2016-2020) using a purposive sampling method following specific criteria. Data were then analyzed using a quantitative approach and a multiple linear regression technique. Results show that company size and investment decision affect firm value positively and significantly. Meanwhile, business diversification negatively and significantly affects firm value. At the same time, capital structure variable makes the relationship between independent and dependent variables stronger.